Thermal shock resistance of ceramic foam sandwich structures: Theoretical calculation and finite element simulation. (30th November 2019) - Li, Z.; Wang, B.L.; Guo, S.L.; Li, J.E.
Abstract: In this paper, the thermal shock resistance of a ceramic foam sandwich (CFS) slab is studied. Two typical thermal shock conditions are considered, i.e., the hot shock and the cold shock. Variations of transient temperature and thermal stress fields with thermal shock time and position are derived. The transient thermal stress intensity factor (SIF) of the thermally induced embedded and edge crack are detected by the developed theoretical model. Simultaneously, the corresponding thermal shock simulation of CFS slab is performed based on finite element (FE) analysis. The results between the presented theoretical model and FE analysis exhibit excellent agreement. Furthermore, the effects of the faceplate thickness and the relative density of the foam core on the thermal shock resistance of CFS slab under hot shock are discussed. Constructive suggestions for the structural optimization design of CFS structures are provided. The study demonstrates the asymmetric fracture behavior under the asymmetric hot shock, and determines the position of the danger zone. Notably, the variations of the influence degree of foam core density on the thermal shock resistance of the CFS slab under cold shock are indicated. The Crack propagation behaviors are investigated and the corresponding crack growth trajectories are provided from the fracture mechanics criterion.